CONVERTING CONVENTIONAL BANKS TO SHARIA BANKS IN ACEH: AN EFFORT TO MAINTAIN A STABLE ECONOMY IN THE COVID-19 OUTBREAK - Iskandar Budiman (Faculty of Islamic Economics and Business, Universitas Islam Negeri Ar-Raniry, 2021)
Based on Aceh Qanun (sharia law) No.11 of 2018 concerning Islamic Financial Institutions, it is required to carry out financial activities based on sharia principles. The decline of the global economy during the Covid-19 outbreak did not dampen the Aceh Government, which declared itself a special province practicing sharia values. Apart from aiming to make a purely Sharia-based region, the conversion of conventional banks to sharia banks is also to stabilize the economy. This study aims to analyze (1) the growth conditions of Islamic banking in Indonesia, (2) the legalization of the Aceh Government Qanun in determining financial institutions operating in Aceh, and (3) the resilience of Islamic banking in facing the global economic downturn during the Covid-19 pandemic. The analysis method used is literature and regulation review. The conclusion that the decentralization system implemented by the Indonesian Government in Islamic banking has not been able to maximize the growth of Islamic banking in Indonesia. Aceh Province, the only province in Indonesia that implements Sharia Law through special autonomy, has its own economic system. The Aceh government issued a Qanun, which obliged economic activities based on sharia principles. Based on Qanun No. 11 of 2018, the operation of Banks in Aceh must be in accord with Sharia. Therefore, entering 2020, the Islamic economy has been running almost perfectly in Aceh by changing conventional banking operations into Islamic banking. Furthermore, Islamic banking in Indonesia can still maintain stable growth when the Indonesian economy slides sharply in the second quarter of 2020 to minus 5.32 percent. This fact proves that increasing the growth of Islamic banking is an important thing to do. The Government should be serious and more consistent in maintaining economic stability and achieving the purposes (maqashid) of Sharia in human life.========================================================================================================ABSTRAK – Konversi Bank Konvensional Menjadi Bank Syariah di Aceh: Upaya Menjaga Stabilitas Perekonomian dalam Wabah Covid-19. Qanun (undang-undang syariat (Islam)) Aceh No 11 Tahun 2018 tentang Lembaga Keuangan Syariah, secara tegas telah mewajibkan lembaga keuangan yang beroperasi di Aceh untuk melaksanakan kegiatannya berdasarkan prinsip syariah. Penurunan ekonomi global di masa pandemi covid-19 tidak menyurutkan langkah Pemerintah Aceh dalam mengimplementasikan kebijakan mensyariahkan seluruh lembaga dan institusi yang berada di Aceh. Walaupun berada di dalam sebuah negara yang tidak menganut paham syariah, Provinsi Aceh telah menyatakan dirinya sebagai sebuah wilayah berkedaulatan syariah Islam. Selain bertujuan untuk menjadikan wilayah yang murni berbasis syariah Islam, konversi bank konvesional menjadi syariah juga bertujuan untuk menstabilkan perekonomian. Penelitian ini bertujuan untuk menganalisis (1) kondisi pertumbuhan perbankan syariah di Indonesia, (2) legalisasi Qanun Pemerintah Aceh dalam menentukan lembaga keuangan yang beroperasi di Aceh, dan (3) ketahanan perbankan syariah dalam menghadapi penurunan perekonomian global di masa pandemi Covid-19. Studi ini menggunakan metode kajian literatur dan analisis regulasi yang menghasilkan kesimpulan yaitu sistem desentralisasi yang dilakukan Pemerintah Indonesia pada perbankan syariah belum dapat memaksimalkan pertumbuhan perbankan syariah di Indonesia. Provinsi Aceh sebagai satu-satunya provinsi di Indonesia yang menjalankan Syariat Islam melalui otonomi khusus mempunyai sistem perekonomian tersendiri. Pemerintah Aceh mengeluarkan qanun yang mewajibkan seluruh kegiatan perekonomian harus berlandaskan prinsip syariah. Berdasarkan Qanun No. 11 Tahun 2018, setiap perbankan yang beroperasi di Aceh haruslah berbentuk syariah. Oleh sebab itu memasuki tahun 2020, perekonomian Islam hampir sempurna telah berjalan di Aceh salah satunya dengan berubahnya operasional perbankan konvensional menjadi perbankan syariah di Provinsi Aceh. Selanjutnya, Perbankan syariah di Indonesia masih mampu menjaga kestabilan pertumbuhannya di saat perekonomian Indonesia meluncur tajam di kuartal II 2020 hingga minus 5,32 persen. Hal ini membuktikan bahwa meningkatkan pertumbuhan perbankan syariah merupakan hal yang penting dilaksanakan, memerlukan keseriusan dan konsistensi terus menerus dari pemerintah demi menjaga kestabilan ekonomi makro dan akan tercapai maqashid syariah pada semua lini kehidupan.